Self-regulated learning interventions with at-risk youth : enhancing adaptability, performance, and well-being - Cleary, Timothy J. (School psychology book series., 2015)
"At-risk students dealing with cognitive, physical, mental health, and environmental challenges often have poor self-regulatory skills. They may struggle with tasks such as planning, goal-setting, and monitoring their own thoughts and actions. This volume describes how teachers, healthcare professionals, and others who work with young people can provide support and helpful strategies to students challenged by problems ranging from ADHD to conduct disorders to language learning deficits to disadvantaged backgrounds. The contributors discuss and illustrate the key components of effective self-regulatory learning, with a particular focus on the central role of feedback loops. Featuring a wide range of nationally known experts who draw on the latest theory- and research-based interventions, the book provides compelling evidence that self-regulated learning interventions are effective and powerful"--Publicity materials. (PsycINFO Database Record (c) 2015 APA, all rights reserved).